PERHITUNGAN HARGA POKOK PRODUKSI DENGAN METODE FULL COSTING UNTUK MENENTUKAN HARGA JUAL PADA UMKM NURUL COOKIES AND BAKERY DESA DUKUHARUM KECAMATAN MEGALUH KABUPATEN JOMBANG - Fahriani, Firda Zulfa; Nisa, Emy Sayidatun (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
Currently there is more and more competition from small businesses. Especially in businesses that sell similar products. This is a threat for small business owners that must be acted upon immediately because it will affect the survival of their business. So business owners must be smarter in determining the selling price for their business products. Before determining the selling price, business owners must calculate the total cost of production first. The aim of this researcher is to analyze the calculation of the cost of production using the full costing method to determine the selling price for the UMKM Nurul cookies and bakery, Dukuharum village, Megaluh sub-district, Jombang regency. To be more conducive, this researcher used a qualitative research method with a case study approach. The data source uses data collection techniques using interviews, observation and documentation. The result of this research is the calculation of the cost of production using the company method to produce IDR 22,590,000. Meanwhile, calculating the cost of production using the full costing method produces IDR 27,519,000. To calculate the selling price using the company method it produces IDR 2,000. Meanwhile, the selling price calculation using the full costing method is Rp. 2,500. Because the calculation uses a calculation method that does not take into account costs that should be included in the detailed calculation of the cost of production, namely labor costs, fixed factory overhead costs such as water and electricity costs and other depreciation costs. Meanwhile, calculating the cost of production using the full costing method calculates all costs in detail.Keywords: Cost of Production, Full Costing Method, Selling Price.